LAYANAN KONSELING DALAM MEMBENTUK KONSEP REMAJA BROKEN HOME - Hasriani Hasriani; Afifatuz Zakiyah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2018)
Self-concept is the whole self-image, which includes a person's perception of themselves, feelings, beliefs, and values associated with him. Self-concept is not taken from birth, but self-concept is formed because of social factors, including environmental factors and parenting parents. Parenting patterns will be very powerful and most important informants in shaping teenagers' self-concept. However, due to broken home conditions, teenagers sometimes find it difficult to conceptualize themselves. So what happens to teenagers broken home tends to self-concept that leads to a negative direction, including teenagers looking down on themselves, consider themselves worthless. Therefore, researchers are interested in conducting counseling service research in the form of broken home adolescent self-counseling. This research is a qualitative research in the form of literature study. The results show that counseling services are appropriate in forming a broken home self-concept that is an individual counseling service with a reality approach. Reality counseling services can be an attempt to form positive teen self-concepts for teenagers broken home.